Learning in and with practice: The insertion of beginning teachers in the career and teaching learning (Revista Contexto & Educação, 2024)
This article is an excerpt from a doctoral research and takes as its object of study the insertion of teachers in the teaching career. It aims to analyze how beginning teachers and educational public policies in recent years, in Brazil, state the professional insertion in teaching. Therefore, the research methodological course was carried out in two stages: the first consisted of official documents analysis that regulate public policies destined to the professional development of teachers, and the second stage sought to gather, through discussion groups, a set of beginning teachers´ speeches who work in the final years of Elementary School, in public schools in the municipality of Caetité, in the State of Bahia. Based on the Foucauldian-inspired discourse analysis, the empirical materiality of the research showed that the insertion in the teaching profession is stated by beginning teachers and by the investigated official documents as a period of teaching learning, in the practice context. Placed as professional-learners, the beginners are guided to learn to deal with the school curriculum and what it establishes about the management of planning, discipline, teaching methodology, evaluation, teaching material, the way of relating to students, with the family and with the community, thus representing a teaching practice in compliance with the contemporary society demands.
Keywords: Beginning teachers; Professional-apprentices; Teaching practice